Observation of a solid phase under measuring the 3He diffusion coefficient in the nanopores of the MCM-41 adsorbent - Birchenko, A. P.; Maidanov, V. A.; Mikhin, N. P.; Sokolov, S. S.; Sopelnyk , Ya. Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2022)
Using nuclear magnetic resonance, the stimulated spin-echo method was applied to measure the diffusion coefficient in a 3He monolayer adsorbed inside cylindrical pores (channel diameter 25 Å) of a new-generation nanostructured adsorbent MCM-41. Helium was let into the sample in small portions, which made it possible to change in a controlled way the coverage of the walls of the cavities in the adsorbent. It is found that the measured dependence of the stimulated spin-echo amplitude on the square of the magnetic field gradient is exponential. The nature of this dependence made it possible to determine the diffusion coefficient in the adsorbed monolayer. The value of this coefficient turned out to be close to the diffusion coefficient in solid helium, which indicates that the first 3He monolayer on the inner surface of the cylindrical cavity is solid. This conclusion was confirmed when calculating the pressure acting on the helium monolayer due to the van der Waals forces from the adsorbent substance.